Augmenting Visual Representation of Affectively Charged Information using Sound Graphs - Calderon, Nadya; Riecke, Bernhard E.; Fisher, Brian (IEEE, 2012)
Within the Visual Analytics research agenda there is an interest on studying the applicability of multimodal information representation and interaction techniques for the analytical reasoning process. The present study summarizes a pilot experiment conducted to understand the effects of augmenting visualizations of affectively-charged information using auditory graphs. We designed an audiovisual representation of social comments made to different news posted on a popular website, and their affective dimension using a sentiment analysis tool for short texts. Participants of the study were asked to create an assessment of the affective valence trend (positive or negative) of the news articles using for it, the visualizations and sonifications. The conditions were tested looking for speed/accuracy trade off comparing the visual representation with an audiovisual one. We discuss our preliminary findings regarding the design of augmented information-representation.
Keywords: 2-page conference paper; 812; Riecke; Riecke_2012; brian-fisher; conferencePapers; iat812; iat812_spring2012; nadya-calderon; short conference paper